2021
DOI: 10.3390/pharmacy9020103
|View full text |Cite
|
Sign up to set email alerts
|

Disposal Practices of Unused and Leftover Medicines in the Households of Dhaka Metropolis

Abstract: Background: This fact-finding study aimed to attain an overall idea and knowledge about medicine disposal practices in Dhaka Metropolitan households. Methods: This mixed study (both quantitative and qualitative) was orchestrated to inspect the household leftover medicine disposal pattern’s governing status. A cross-sectional survey was conducted following a structured questionnaire and key informant interview with a household person and in-depth interviews with the top pharmaceutical and government officials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 65 publications
2
9
0
1
Order By: Relevance
“…Such disposal would be through the general-purpose bin (58; 77.0%), pouring them down the sink (11; 14.3%), via the toilet (4; 6.1%) and dumping in the gutter (2; 2.6%). These improper disposal practices witnessed in our study have been reported in several studies on the disposal of leftover and expired medicines among the households (Azmi Hassali and Shakeel, 2020; Begum et al, 2021; Kahsay et al, 2020; Kassahun and Tesfaye, 2020; Marwa et al, 2021; Osei-djarbeng et al, 2015; Wang et al, 2021). Furthermore, a review by Makki et al (2019) reported that unwanted and expired medicines are often disposed of through the garbage trash, toilets, sink and given to relatives and friends.…”
Section: Resultssupporting
confidence: 77%
“…Such disposal would be through the general-purpose bin (58; 77.0%), pouring them down the sink (11; 14.3%), via the toilet (4; 6.1%) and dumping in the gutter (2; 2.6%). These improper disposal practices witnessed in our study have been reported in several studies on the disposal of leftover and expired medicines among the households (Azmi Hassali and Shakeel, 2020; Begum et al, 2021; Kahsay et al, 2020; Kassahun and Tesfaye, 2020; Marwa et al, 2021; Osei-djarbeng et al, 2015; Wang et al, 2021). Furthermore, a review by Makki et al (2019) reported that unwanted and expired medicines are often disposed of through the garbage trash, toilets, sink and given to relatives and friends.…”
Section: Resultssupporting
confidence: 77%
“…This is a clear indication that the majority of the respondents were not aware of the medication take-back program. This result is comparable to the study conducted in the households of Dhaka Metropolitan, Bangladesh in which 72% of respondents were willing to participate in the medicines take-back program [27]. Similarly, in Tanzania [28] and Ethiopia [29], 96% and 78% of the participants, who did not know about the medicines take-back system, expressed willingness to participate in the program after the principle was explained to them respectively.…”
Section: Discussionsupporting
confidence: 64%
“…These items were widely acknowledged by respondents in the present survey: small paper bags (42.6%), plastic bottles (49.1%), and small plastic bags (67.9%). Such packaging waste materials were not considered or mentioned in several studies conducted in South Africa [ 8 , 9 ] and even abroad [ 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the results showing the different degrees of willingness to return unused medicines and associated accessories to hospitals and pharmacies, most respondents expressed a positive disposition towards playing a meaningful role in such medicine take-back schemes. However, the implementation of such programs in many developing countries is fraught with implementation pitfalls due to a lack of environmental awareness, necessary infrastructure, and willingness to pay for such programs [ 41 , 54 , 55 , 56 ]. This constraint also applies to South Africa, where there is no well-defined national legislative and regulatory framework to deal with discarded HPWs in a sustainable manner.…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 99%